2015
DOI: 10.4238/2015.august.21.14
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of melatonin receptors in chicken ovarian follicles affected by monochromatic light

et al.

Abstract: ABSTRACT. Artificial illumination is an important exogenous factor in the control of many physiological and behavioral processes as well as an important environmental factor in the management of laying hens. Melatonin receptors are members of the G protein-coupled receptor family. The hormone melatonin is secreted primarily by the pineal gland, with highest levels occurring during the dark period of a circadian cycle. The aim of this study was to examine the effect of monochromatic light on chicken egg reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…MT1 and MT2 were expressed in both the thecal and granulosa layers30. It was reported that MT1 and MT3 were negatively correlated with the total number of eggs yielded in hens 300 days of age that were exposed to different monochromatic light31. We observed that melatonin implantation did not influence the expression of ovarian MT1 but up-regulated the expression of MT2 .…”
Section: Discussionmentioning
confidence: 53%
“…MT1 and MT2 were expressed in both the thecal and granulosa layers30. It was reported that MT1 and MT3 were negatively correlated with the total number of eggs yielded in hens 300 days of age that were exposed to different monochromatic light31. We observed that melatonin implantation did not influence the expression of ovarian MT1 but up-regulated the expression of MT2 .…”
Section: Discussionmentioning
confidence: 53%
“…There is also differential photoperiodic regulation of melatonin subtype receptor expression in tropical bird testes ( Perdicula asiatica , see [ 134 ]). The effects of monochromatic light on ovarian melatonin subtype receptor expression were studied in chickens [ 135 ]. Hens that were housed in red (660 nm) light expressed Mel1a and Mel1c at significantly higher levels than all other groups [ 135 ].…”
Section: Melatonin Bindingmentioning
confidence: 99%
“…The effects of monochromatic light on ovarian melatonin subtype receptor expression were studied in chickens [ 135 ]. Hens that were housed in red (660 nm) light expressed Mel1a and Mel1c at significantly higher levels than all other groups [ 135 ]. Furthermore, hens housed in blue (480 nm) light laid significantly more eggs than all other groups [ 135 ].…”
Section: Melatonin Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular understanding of circadian rhythms is almost exclusively related to terrestrial species. A number of studies have revealed that the expression of some clock genes, such as per, cry, and melatonin, is affected by both daylight and moonlight, suggesting interconnections between solar and lunar rhythms in animals (Levy et al, 2007;Sugama et al, 2008;Li et al, 2015a). For marine species, molecular components of "marine rhythms" are essential to understand how marine species detect solar and lunar cycles and translate this into the sequence of physiological processes that result in the maturation of gametes and determine the timing of spawning.…”
Section: Introductionmentioning
confidence: 99%